Are cultural or psychosocial factors associated with patient‐reported outcomes at the conclusion of kidney transplant evaluation?. Issue 11 (31st August 2022) - Swift, Samuel L.; Leyva, Yuri; Wang, Shu; Chang, Chung‐Chou H.; Dew, Mary Amanda; Shapiro, Ron; Unruh, Mark; Kendall, Kellee; Croswell, Emilee; Peipert, John Devin; Myaskovsky, Larissa
Abstract: Background: Kidney transplant evaluation (KTE) is a period marked by many stressors for patients, which may lead to poorer patient‐reported outcomes (PROs). Research on the association of cultural and psychosocial factors with PROs during KTE is lacking, even though cultural and psychosocial variables may mitigate the relationship between acceptance status and PROs. Methods: Using a prospective cohort study of 955 adults referred for KTE, we examined whether cultural factors and psychosocial characteristics, assessed at the initiation of KTE, are associated with PROs at KTE completion, controlling for demographics and medical factors. Also, we analyzed whether these factors moderate the relationship between transplant acceptance status and PROs. Results: In multivariable regression models, a stronger sense of mastery was associated with higher physical and mental QOL. A stronger sense of self‐esteem was associated with higher kidney‐specific QOL. Depression was associated with a lower mental QOL, but only in those who were accepted for transplant. Having low levels of external locus of control was associated with better mental QOL in those who were not accepted for transplant. Higher anxiety was associated with poorer kidney‐specific QOL among those who were not accepted for KT, but trust in physician was only associated with greater satisfaction in transplant clinic service for those who were accepted for KT. Conclusions: Targeting interventions to increase patient mastery and external locus of control, and reduce depression and anxiety in patients undergoing kidney transplant evaluation may be useful approaches to improve their experience during this stressful period.